Would primary healthcare professionals prescribe a polypill to manage cardiovascular risk? A qualitative interview study. Issue 3 (25th March 2013) - Virdee, Satnam K; Greenfield, Sheila M; Fletcher, Kate; McManus, Richard J; Hobbs, F D Richard; Mant, Jonathan
Abstract : Objectives: A 'polypill' containing both blood pressure-lowering and cholesterol-lowering drugs could prevent up to 80% of cardiovascular disease events. Since little is known about the attitudes of primary healthcare professionals to use of such a pill for cardiovascular disease prevention, this study aimed to investigate opinions. Design: Semistructured interviews were conducted with participants. A qualitative description approach was used to analyse and report the results. Setting: Participants were recruited from nine primary care practices in Birmingham. Participants: Sixteen healthcare professionals (11 primary care physicians and 5 practice nurses) were selected through purposive sampling to maximise variation of characteristics. Outcome measures: Outcome measures for this study were: the attitude of healthcare professionals towards the use of a polypill for primary and secondary cardiovascular disease prevention; their views on monitoring the drug; and the factors influencing their willingness to prescribe the medication. Results: Healthcare professionals expressed considerable concern over using a polypill for primary prevention for all people over a specific age, although there was greater acceptance of its use for secondary prevention. Regularly monitoring patients taking the polypill was deemed essential. Evidence of effectiveness, patient risk level and potential medicalisation were key determinants in willingness to prescribe such a pill. Conclusions: Primary healthcare professionals have significant concerns about the use of a polypill, particularly in the prevention of cardiovascular disease in people who are not regarded as being at 'high risk'. If a population-based polypill strategy is to be successfully implemented, healthcare professionals will need to be convinced of the potential benefits of a drug-based population approach to prevention.